2019
DOI: 10.1080/1331677x.2019.1627893
|View full text |Cite
|
Sign up to set email alerts
|

Customer satisfaction, loyalty, knowledge and competitiveness in the food industry

Abstract: The subject of this article is customer satisfaction, loyalty, knowledge and business competitiveness from the perspective of a food-industry customer. This article aims to analyse the relationship between customer satisfaction, customer loyalty, product knowledge, business competitiveness and other selected factors which influence customer satisfaction. The research is aimed at customers who purchase the product in question repeatedly and have personal experience with this product. The research was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 40 publications
(56 reference statements)
1
45
0
4
Order By: Relevance
“…When customers are satisfied with the products or services they have purchased and used, the customers will be loyal to the company's products and services therefore they will be loyal to the company. This is proven by previous researzch in the following industries: banking [2][3][4][5][6][7][8], airlines [9], education [10], entertainment [11], food [12][13][14], hospital [15], hotel [16], manufacture [17], retail [18][19][20][21], shipping [22][23], telecommunication [24][25][26][27]. Those research conclude that customer satisfaction has a significant positive effect on customer loyalty.…”
Section: Introductionsupporting
confidence: 57%
“…When customers are satisfied with the products or services they have purchased and used, the customers will be loyal to the company's products and services therefore they will be loyal to the company. This is proven by previous researzch in the following industries: banking [2][3][4][5][6][7][8], airlines [9], education [10], entertainment [11], food [12][13][14], hospital [15], hotel [16], manufacture [17], retail [18][19][20][21], shipping [22][23], telecommunication [24][25][26][27]. Those research conclude that customer satisfaction has a significant positive effect on customer loyalty.…”
Section: Introductionsupporting
confidence: 57%
“…Review of a current state of the art using articles and studies of other authors point out at following factors within their influence on customer behaviour and preferences, namely the level of food literacy, product knowledge or purchasing power (Dudek, 2019;Erokhin, 2017;Ronto, Ball, Pendergast & Harris, 2016;Savelli, Murmura, Liberatore, Casolani & Bravi, 2019;Suchánek & Králová, 2019). Companies respond to these factors by identification of changes in established consumer behaviour in order to maintain their competitiveness that can be measured among all by financial performance indicators.…”
Section: Resultsmentioning
confidence: 99%
“…Customers will be more loyal when they receive excellent food, the fast service delivery of eatables, a pleasant physical environment, and a memorable dining experience. (Petr & Maria, 2019), found that, customers became more loyal when they purchase more of the same product. The customer gains more product knowledge when they repeat purchase.…”
Section: Customer Satisfaction and Customer Loyaltymentioning
confidence: 99%